STORIES PROJECTED FROM THE TITLES: EXPECTATIONS FULFILLED (OR NOT!) IN THE TEXT - Arruda Doná, Beatriz (Revista Sinergia, 2019)
This article aims to emphasize the importance of the title in texts, especially in argumentative texts. With the Cognitive Linguistics theoretical framework, we show how prior narratives are built from elements of the title and how we create expectations often met (or not!) by the reader at the end of the text. Thus, overlapping narratives, suspense, expectations, or the argumentative text is constructed as a great narrative that also puts the author-reader and their stories in dialogue. This dynamic occurs through analogical cognitive processes that involve metaphors and metonymies in the construction of meanings specifically related to the way we see the world and dialogue with it. This work has special pedagogical appeal as it is born from the need to teach high school students not only to argue critically and creatively, but also to place titles in their texts. A challenge faced in the classroom is for students to value the construction of the title, its origin, and its importance in the construction of the text’s meaning through to the text’s conclusion. Referring to the author's previous research in her doctoral dissertation and her recent practices as a high school writing and pre-college entrance exam teacher, this paper brings together these two points and shows in a contextualized and sequential way (through the analysis of the title of the author's doctoral thesis and a college entrance exam essay by one of her students) how writers intuitively place the title in their texts and how, in a systematic and intentional way, we can work with this intuitive nature of language to ensure titles, texts, and creative narratives. More than that we look at how to ensure that from a doctoral dissertation to a college entrance exam essay, the text does not start with the first paragraph written, but with the title and the stories it awakens.